Commentary: Data storytelling to aid health system decision-makers with population health issues for a specific location (Journal of Health Sciences, 2022)
Modern society is awash in data for health science, health system, and public health decision-making. These public data are often presented in various formats: Data tables, reports with data and bar charts, press releases with data, dashboards of key performance indicators, the traditional professional paper with data table and statistical results, etc. Software can display these data in various ways. The tacit assumption is that the reader/consumer of the data has the means to interpret these often complex health data for individual use and professional decision-making. We do not think that it is reasonable to make this assumption in all situations. Instead, maybe those of us who collect and analyze health data should include data storytelling as a way to make it easier for health system decision-makers to know and appreciate the next steps to be taken in the decision-making process given the data we prepared. The interpretation of data for action using a charticle and other techniques of infographics and health data storytelling may be more useful to health system decision-makers than the presentation of detailed facts and data and a scientific interpretation of those facts and data. This commentary illustrates the process of data storytelling using a charticle to help health system decision-makers interpret health data and use it as a foundation for action.